Identifying the most suitable learning techniques based on cognitive and physiological behavior - Asanka D. Dharmawansa; R.A.M. Madhuwanthi (The Open University of Sri Lanka, 2024)
Numerous learning platforms and teaching methods have emerged in recent years. Identifying effective approaches is crucial for enhancing the productivity of education. This study aimed to determine the most effective learning tactics for small face-to-face management classes in tertiary education, based on students' cognitive and physiological behavior. Eight management students with varying academic backgrounds were selected through purposive sampling for the experiment which consists of active and passive learning sessions. The lecture served as the passive learning session. Problem-Based Learning (PBL) activities were conducted both individually and in groups, with another group activity following the lecture, representing the active learning sessions. Brain activity was measured using electroencephalogram (EEG) to identify Beta (β) waves. Physiological data was collected using a Galvanic Skin Response (GSR) sensor to measure sweat gland activity. Additionally, fluctuation in heart rate variation was captured through Electrocardiogram (ECG) signals. Exploratory data analysis was employed to analyse the bio-signal data. The group activity after the lecture resulted in the highest levels of cognitive and physiological engagement among participants. While students performed better in active learning sessions overall, individual activities were less effective compared to group-based activities. This study suggests that even though passive learning, like lectures, may have some value, a combination of passive and active learning strategies may yield the most productive learning environment for small group management courses in tertiary education.